A possible mechanism of metabolic regulation in Gibberella fujikuroi using a mixed carbon source of glucose and corn oil inferred from analysis of the kinetics data obtained in a stirrer tank bioreactor. (4th July 2013) - Rios‐Iribe, Erika Y.; Hernández‐Calderón, Oscar M.; Reyes‐Moreno, C.; Contreras‐Andrade, I.; Flores‐Cotera, Luis B.; Escamilla‐Silva, Eleazar M.
Abstract : A nonstructured model was used to study the dynamics of gibberellic acid production in a stirred tank bioreactor. Experimental data were obtained from submerged batch cultures of Gibberella fujikuroi (CDBB H‐984) grown in varying ratios of glucose‐corn oil as the carbon source. The nitrogen depletion effect was included in mathematical model by considering the specific kinetic constants as a linear function of the normalized nitrogen consumption rate. The kinetics of biomass growth and consumption of phosphate and nitrogen were based on the logistic model. The traditional first‐order kinetic model was used to describe the specific consumption of glucose and corn oil. The nitrogen effect was solely included in the phosphate and corn oil consumption and biomass growth. The model fit was satisfactory, revealing the dependence of the kinetics with respect to the nitrogen assimilation rate. Through simulations, it was possible to make diagrams of specific growth rate and specific rate of substrate consumptions, which was a powerful tool for understanding the metabolic interactions that occurred during the various stages of fermentation process. This kinetic analysis provided the proposal of a possible mechanism of regulation on growth, substrate consumptions, and production of gibberellic acid (GA3 ) in G. fujikuroi . © 2013 American Institute of Chemical Engineers Biotechnol. Prog ., 29:1169–1180, 2013